Differential gene expression analysis in Enchytraeus albidus exposed to natural and chemical stressors at different exposure periods - Novais, Sara C. (2019)
The soil oligochaete Enchytraeus albidus is a standard test organism used in biological testing for Environmental Risk Assessment (ERA). Although effects are known at acute and chronic level through survival, reproduction and avoidance behaviour endpoints, very little is known at the sub-cellular and molecular levels. In this study, the effects of soil properties (clay, organic matter and pH) and of the chemicals copper and phenmedipham were studied on E. albidus gene expression, during exposure periods of 2, 4 and 21 days, using DNA microarrays based on a normalised cDNA library for this test species (Amorim et al. 2011). The main objectives of this study were: (1) to assess changes in gene expression of E. albidus over time, and (2) to identify molecular markers for natural and chemical exposures. Results showed an influence of exposure time on gene expression. Transcriptional responses to phenmedipham were seen at 2 days while the responses to copper and the different soils were more pronounced at 4 days of exposure. Some genes were differentially expressed in a stress specific manner and, in general, the responses were related with effects in the energy metabolism and cell growth.